The Role Of Human Resource Development (HRD) In The 5.0 Era - Siti Dena Zahar; Filika Millenia; Fitri Amanda Syahria; Muhammad Rizki Maulana; Siti Aisyah Binti Panatik; Irmawati Binti Norazman (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Human resources can also be referred to as personnel, labor, workers, employees, human potential as the driving force of the organization in realizing its existence. Society 5.0 is considered a concept built on the basis of humans and technology. In this era, people will be faced with a life accompanied by technological sophistication. This study aims to analyze the role of human resource development in the 5.0 era. The role of human resources as one of the elements in the organization can be interpreted as humans who work in an organization. This research uses a qualitative descriptive method with a literature approach or literature review. The research data was obtained through literature study and data analysis from various scientific sources. The results show that the role of human resource development in the 5.0 era is to digitilize the work environment based on technology, collaboration with cyber systems, flexible work processes that can be adjusted to customer needs, mental tasks and work teams.